Chromatin tethering to the nuclear envelope by nuclear actin filaments: a novel role of the actin cytoskeleton in the Xenopus blastula. (20th March 2017) - Oda, Haruka; Shirai, Natsuki; Ura, Naoko; Ohsumi, Keita; Iwabuchi, Mari
Abstract : The Xenopus oocyte is known to accumulate filamentous or F‐actin in the nucleus, but it is currently unknown whether F‐actin also accumulates in embryo nuclei. Using fluorescence‐labeled actin reporters, we examined the actin distribution in Xenopus embryonic cells and found that F‐actin accumulates in nuclei during the blastula stage but not during the gastrula stage. To further investigate nuclear F‐actin, we devised a Xenopus egg extract that reproduces the formation of nuclei in which F‐actin accumulates. Using this extract, we found that F‐actin accumulates primarily at the subnuclear membranous region and is essential to maintain chromatin binding to the nuclear envelope in well‐developed nuclei. We also provide evidence that nuclear F‐actin increases the structural stability of nuclei and contributes to chromosome alignment on the mitotic spindle at the following M phase. These results suggest the physiological importance of nuclear F‐actin accumulation in rapidly dividing large Xenopus blastula cells. Abstract : While nuclear F‐actin accumulates in Xenopus oocytes, it is unknown whether it does so in embryos. Using fluorescence‐labeled actin reporters and Xenopus egg extracts, we demonstrate that F‐actin accumulates in blastula nuclei, promoting chromatin–nuclear envelope binding, nuclear structural stability and M‐phase mitotic chromosome alignment.